PERFORMANPERTUMBUHANAYAMPEDAGING DENGAN PENGGUNAAN LUMPUR SAWITFERMENTASI DALAM RANSUM - Hasan, Asmira; Tarsono, Tarsono; Nirwana, Nirwana (FAPETKAN UNTAD, 2016)
Palm sludge is a by-product of the palm oil processing that is quite numerous and still contains nutrients that can be utilized as an alternative feed ingredient for poultry. However, high crude fiber content resulted in the utilization of alternative feed ingredients for poultry is limited. The fermentation process can increase nutritive value of the palm sludge. This research aimed to study the use effect of the fermented palm sludge (FPS)in the ration on the growth performance of broiler. The research has been conducted in the animal teaching farm of theAnimal Husbandry Faculty starting from October 9th to November 13th, 2013 using 80 DOCs (day old chickens) produced by PT. Satwa Utama Raya, Makassar. Those DOCswere raised in the 20 cages that each has a size of 60x60x90 cm. Each cage was placed by buckets of ration and drinking water. A complete randomizeddesign was used in this research with 5 treatments and 4 replications.Â The treatments were R0 (ration without FPS), R1 (ration with 2.5% FPS), R2 (ration with 5.0% FPS), R3 (ration with 7.5% FPS), R4 (ration with 10.0% FPS). The research parameters were feed consumption, body weight gain, and feed conversion.The result showed that treatments affected non-significantly (P>0.05) on the three observed variables. It was concluded that the fermented palm sludge still can be used up to 10% in the broilerâ€™s ration.Key words: broiler, fermented palm sludge, growth performance